ANALISIS YURIDIS PENGADAAN BARANG/JASA YANG DILAKUKAN DINAS PENDIDIKAN KOTA TANJUNGBALAI DITINJAU DARI PERATURAN PRESIDEN NOMOR 54 TAHUN 2010 TENTANG PENGADAAN BARANG/JASA PEMERINTAH - DENNY SANJAYA; RAMLI SIREGAR; WINDHA WINDHA (Universitas Sumatera Utara, 2013)
The government did many efforts to enhance the quality of human recources. One of the effort is by providing the instances with good things and service that involvies some parties, such as the user and the provider. In fact, there was so many rules that regulates the government activities in this case, that sometimes makes some uncertain legal inside it. The rules are so old and not update but government still using them to maintain the governmental process. The government doesn’t has the absolute responsibility in providing the instances with good things and services. The also helped by the parliament in decided and validatedthe RAPBN. The region government is also helped by the region parliament. Provides the instances with good things and services will be held if it was noted in RAPBN/RAPBD which made by the government that also helped by the region parliament. The RAPBN/RAPBD will become APBN/APBD. In this thesis that titled Juridice Analysis About Provides Things and Services That Held by the Tanjungbalai Educetion Departement reviewed from the President Regulation Nomor 54 Tahun 2010, the President Regulation Nomor 54 Tahun 2010 was change become President Regulation Nomor 70 Tahun 2012 about Providing things and services. The regulation manage about the principal and ethical in providing goverment things and services. In the president regulation about providing government things and services includes of the practice steps from the variety methodes. The contract is one of the important part in providing government things and services. Key words : Pemerintah, pengadaan barang/jasa, kontrak.